2019
DOI: 10.47114/j.agroped.2018.jun10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Levels of Nitrogen and Sulphur on Yield and Nutrient Uptake by Fennel (Foeniculum vulgare Mill.)

Abstract: An experiment comprising of four levels of nitrogen viz., 0, 60, 90 and 120 kg ha-1 and three levels of sulphur viz., 0, 20 and 40 kg ha-1 was conducted infactorial randomized block design, replicated thrice during rabi 2016-17 at the Instructional Farm, Department of Agronomy, College of Agriculture, Junagadh Agricultural University, Junagadh to study the influence of N and S on yield and uptake of nutrients by fennel. The experimental medium deep black soil was clay in texture and had pH 8.06 and EC 0.41 dSm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…It also proved the finding of Azizi et al and Nath et al [11 and 12] in Ajowain and Tehlan et al [13] in coriander.At the same time, Kucha et al [14] observed a significant maximum number of umbels per plant in fennel on applying 120 kg [15 and 16] observed an increase in the number of umbellets per umbel with an increased nitrogen dose of up to 120 kg N ha -1 in fennel crop. It might be due to the greater availability of photosynthates, metabolites, and nutrients for the development of reproductive structures as nitrogen played an essential role in chlorophyll synthesis, which is the main absorber of light energy needed for photosynthesis and thus, increased photosynthates production and translocation in the plant.…”
Section: Effect Of Nitrogen Fertilizer Level On Yield Attributes and ...mentioning
confidence: 98%
“…It also proved the finding of Azizi et al and Nath et al [11 and 12] in Ajowain and Tehlan et al [13] in coriander.At the same time, Kucha et al [14] observed a significant maximum number of umbels per plant in fennel on applying 120 kg [15 and 16] observed an increase in the number of umbellets per umbel with an increased nitrogen dose of up to 120 kg N ha -1 in fennel crop. It might be due to the greater availability of photosynthates, metabolites, and nutrients for the development of reproductive structures as nitrogen played an essential role in chlorophyll synthesis, which is the main absorber of light energy needed for photosynthesis and thus, increased photosynthates production and translocation in the plant.…”
Section: Effect Of Nitrogen Fertilizer Level On Yield Attributes and ...mentioning
confidence: 98%